MicroRNA-328 Contributes to Adverse Electrical Remodeling in Atrial Fibrillation - Lu, Yanjie; Zhang, Ying; Wang, Ning; Pan, Zhenwei; Gao, Xu; Zhang, Fengmin; Zhang, Yong; Shan, Hongli; Luo, Xiaobin; Bai, Yunlong; Sun, Lihua; Song, Wuqi; et al. (Circulation (New York, N.Y.), 2010)
A characteristic of both clinical and experimental atrial fibrillation (AF) is atrial electric remodeling associated with profound reduction of L-type Ca(2+) current and shortening of the action potential duration. The possibility that microRNAs (miRNAs) may be involved in this process has not been tested. Accordingly, we assessed the potential role of miRNAs in regulating experimental AF. The miRNA transcriptome was analyzed by microarray and verified by real-time reverse-transcription polymerase chain reaction with left atrial samples from dogs with AF established by right atrial tachypacing for 8 weeks and from human atrial samples from AF patients with rheumatic heart disease. miR-223, miR-328, and miR-664 were found to be upregulated by >2 fold, whereas miR-101, miR-320, and miR-499 were downregulated by at least 50%. In particular, miR-328 level was elevated by 3.9-fold in AF dogs and 3.5-fold in AF patients relative to non-AF subjects. Computational prediction identified CACNA1C and CACNB1, which encode cardiac L-type Ca(2+) channel α1c- and β1 subunits, respectively, as potential targets for miR-328. Forced expression of miR-328 through adenovirus infection in canine atrium and transgenic approach in mice recapitulated the phenotypes of AF, exemplified by enhanced AF vulnerability, diminished L-type Ca(2+) current, and shortened atrial action potential duration. Normalization of miR-328 level with antagomiR reversed the conditions, and genetic knockdown of endogenous miR-328 dampened AF vulnerability. CACNA1C and CACNB1 as the cognate target genes for miR-328 were confirmed by Western blot and luciferase activity assay showing the reciprocal relationship between the levels of miR-328 and L-type Ca(2+) channel protein subunits. miR-328 contributes to the adverse atrial electric remodeling in AF through targeting L-type Ca(2+) channel genes. The study therefore uncovered a novel molecular mechanism for AF and indicated miR-328 as a potential therapeutic target for AF.